Automated Data Processing for Monitoring Based on Median Algorithm - Yan Du; Mowen Xie; Xiaoli Yang; Qiuqiang Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
As introduction of the automation equipment, hardware automation level on reservoir has greatly improved. For the restriction of the software performance and technical personnel, data reorganization far failed to meet the requirements of hardware. Base on the research on domestic and foreign technique, it is concluded that a set of data transformation methods suitable for the automation system of the small and medium-sized dams. Through the median denoising processing and eigenvalue automatic statistical techniques, a large amount of data can be screened and filtered. The method can solve practical engineering problems and meet the need of automation equipment.